Efficacy and Safety of CVO PLUS CURATIF Capsules, Malagasy Improved Traditional Medication for Treating COVID-19: A Randomized, Double- Blind, Placebo-Controlled Trial - Rakotosaona, Rianasoambolanoro; Mioramalala, Sedera A.; Rakotoarisoa, Malala Arinomenjanahary; Rakotondrandriana, Antsa; Randrianarivo, Emmanuel; Rabetokotany, Felana; Rakoto, Fanomezantsoa; Razafimandimby, Dominique; Ravelo, Arsène; Maminiaina, Fridolin; et al. (Archives of Clinical and Biomedical Research, 2022)
Background: Only a few drugs are currently approved to treat COVID-19. CVO PLUS CURATIF (CVO+C) is a capsule formulation of artemisinin and 1,8-cineole, two plant-derived compounds with anti-inflammatory and antiviral properties in vitro. These compounds have been repurposed for potential use as an oral COVID-19 treatment. Methods: We performed a phase 3 randomized clinical trial on patients over the age of 18 years with SARS-CoV-2 infection and mild-tomoderate symptoms. Patients were randomly assigned to receive CVO+C (3 capsules per day) or placebo. The primary outcomes were the proportion of patients testing negative for SARS-CoV-2 on day 28 and the absence of serious adverse events. Secondary outcomes included recovery time and biological markers. Results: In total, 1,576 individuals were screened, 339 of whom met the inclusion criteria. After data cleaning, 132 were from the CVO+C arm and 144 from the placebo arm. Treatment efficacy differed significantly (p = 0.011) between the CVO+C arm (87.1%, 95% CI: 81.3%-92.9%, with 70.45% of patients cured by day 14) and the placebo arm (75.0%, 95% CI: 67.8%-82.1%), with an OR of 2.25. The median time to recovery was 14 days for the CVO+C group and 21 days for the placebo group. There were 72 mild and moderate adverse events, 14 severe adverse events, and no serious adverse events in either group. Conclusions: CVO+C was effective for the treatment of mild-to-moderate COVID-19. None of the patients in the CVO+C arm developed the severe form of COVID-19. Patients’ liver, kidney, and metabolic functions were preserved.